Significance of personal relationship on life insurance industry. - Chia, Meng Hwee. (2008)
The strong influence of customer relationships on sales closures has gained much attention in the research arena. This paper attempts to establish whether relationship development and the selected factors play a dominant role in the sales performance of life insurance agents in Singapore.